The Influence of Work Environment and Talent Management Through Employee Performance Productivity On The Implementation of Employee Work Programs - Raditya Wibowo; Ahmad Mukhlis; Icin Quraisyn (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study aims to analyze the influence of the work environment and talent management on the implementation of work programs through employee performance productivity at PT Krakatau Bandar Samudera, Cilegon City. The study used a quantitative approach with a survey method. The study population was 440 employees, while the sample was 210 respondents determined using a stratified random sampling technique. Data collection was carried out through a questionnaire with a five-level Likert scale, then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4.0. The results showed that the work environment had a positive and significant effect on the implementation of work programs with a coefficient of 0.932 and on employee performance productivity of 0.841. Talent management also had a positive and significant effect on the implementation of work programs of 0.802 and on employee performance productivity of 0.158. Employee performance productivity had a significant effect on the implementation of work programs, but showed a negative direction with a coefficient of -0.734. Employee performance productivity also acts as an intervening variable in the relationship between the work environment and talent management and work program implementation, with indirect coefficients of -0.617 and -0.116, respectively. The findings demonstrate the importance of the work environment and talent management in supporting the implementation of a company's work program.